The intersection molecule MDA5 in Cancer and COVID-19 - Jin, Renjing; Cao, Xiaoqing; Lu, Mingjun; Gao, Qing; Ma, Teng (Frontiers in Immunology, 2022)
The connections between Pattern recognition receptors (PRRs) and pathogen-associated molecular patterns (PAMPs) constitutes the crucial signaling pathways in the innate immune system. Cytoplasmic nucleic acid sensor melanoma differentiation-associated gene 5 (MDA5) serves as an important pattern recognition receptor in the innate immune system by recognizing virus RNA. MDA5 also plays a role in identifying the cytoplasmic RNA from damaged or dead cancer cells or autoimmune diseases. MDA5’s recognition of RNA triggers innate immune response, induces interferon (IFN) response and a series of subsequent signaling pathways to produce immunomodulatory factors and inflammatory cytokines. Here we review the latest progresses of MDA5 functions in triggering anti-tumor immunity by sensing cytoplasmic dsRNA, and recognizing SARS-CoV-2 virus infection for antiviral response, in which the virus utilizes multiple ways to evade the host defense mechanism.